Trichinella spiralis, potential model nematode for epigenetics and its implication in metazoan parasitism - GAO, Fei; WANG, Rui; Liu, Mingyuan (Frontiers in Physiology, 2014)
The recent discovery of DNA methylation in the nematode T. spiralis may raise the possibility of using it as a potential model organism for epigenetic studies instead of C. elegans, which is deficient in this important epigenetic modification. In contrast to the free-living nematode C. elegans, T. spiralis is a parasitic worm that possesses a complicated life cycle and undergoes a complex developmental regulation of genes. We emphasise that the differential methylomes in the different life-history stages of T. spiralis can provide insight on how DNA methylation is triggered and regulated. In particular, we have demonstrated that DNA methylation is involved in the regulation of its parasitism-related genes. Further computational analyses indicated that the regulatory machinery for DNA methylation can also be found in the T. spiralis genome. By a logical extension of this point, we speculate that comprehensively addressing the epigenetic machinery of T. spiralis may help to understand epigenetics in invertebrates. Furthermore, considering the implication of epigenetics in metazoan parasitism, using T. spiralis as an epigenetic model organism may further contribute to drug development against metazoan parasites.